‘Forget me (not)?’ – Remembering Forget-Items Versus Un-Cued Items in Directed Forgetting - Zwissler, Bastian; Schindler, Sebastian; Fischer, Helena; Plewnia, Christian; Kissler, Johanna M. (Frontiers in Psychology, 2015)
Humans need to be able to selectively control their memories. Here, we investigate the underlying processes in item-method directed forgetting and compare the classic active memory cues in this paradigm with a passive instruction. Typically, individual items are presented and each is followed by either a forget- or remember-instruction. On a surprise test of all items, memory is then worse for to-be-forgotten items (TBF) compared to to-be-remembered items (TBR). This is thought to result from selective rehearsal of TBR, or from active inhibition of TBF, or from both. However, evidence suggests that if a forget instruction initiates active processing, paradoxical effects may also arise. To investigate the underlying mechanisms, four experiments were conducted where un-cued items (UI) were introduced and recognition performance was compared between TBR, TBF and UI stimuli. Accuracy was encouraged via a performance-dependent monetary bonus. Across all experiments, including perceptually fully matched variants, memory accuracy for TBF was reduced compared to TBR, but better than for UI. Moreover, participants used a more conservative response criterion when responding to TBF stimuli. Thus, ironically, the F cue results in active processing, but this does not have inhibitory effects that would impair recognition memory beyond a un-cued baseline condition. This casts doubts on inhibitory accounts of item-method directed forgetting and is also difficult to reconcile with pure selective rehearsal of TBR. While the F-cue does induce active processing, this does not result in particularly successful forgetting. The pattern seems most consistent with the notion of ironic processing.